Limas House Horizontal Proportion and Dulang Module: The Collectivism of Austronesian, Buddhism, Hinduism, Taoism, and Islam in Palembang History - Ibnu Aziz; Ahmad Malik Abdul Aziz (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
The development of Palembang city is progressing rapidly while traditional limas houses are increasingly rare. As a result, the local context regarding the rules for building limas has become rare and not documented. This is unfortunate considering that limas have architectural and cultural records related to the history of Palembang City, starting from the Austronesian, Hindu-Buddhist, and Taoist to the Islamic period. This study seeks to find the rules of horizontal proportion used in the construction of limas and their relation with the cultural values of society. Researchers explored the dulang,a circular container that holds plates for serving food to eight people, as the base module that builds the floor area of a limas. Data were collected from 50 limas in Palembang City, consisting of 20 four-bengkilas limas (4BL) and 30 three-bengkilas limas (3BL). The results show that 3BL is generally made with four dulang on the front and seven dulang on the side. In comparison, 4BL are built with five dulang on the semi-public side of the bengkilas, three dulang on the back, and seven dulang on the side. Furthermore, the researcher shows that this proportion rule is changed across time in line with the smaller house size. This change signifies the decline of collectivism from a concrete principle to a merely symbolic one. This decline is associated with an increase in the individual's economy and standard of living. This research has implications for efforts to standardize the Palembang limas house model for conserving the city's cultural heritage.